Analysis of approaches, theories and concepts of cinematherapy in working with children with mental disorders. Part 1 - Dmitry Vyacheslavovich Bosov; Ruslan Yuryevich Dolya (Вестник Майкопского государственного технологического университета)
The problem of analyzing the approaches, theories and concepts of cinema therapy in working with children with mental disorders is an urgent problem. The article analyzes the approaches, theories and concepts of cinema therapy, reveals their essence and gives characteristics in relation to work with children with mental disabilities. The subject of the research is the analysis of the approaches, theories and concepts of cinema therapy in relation to work with children with mental disorders. The object of the research is the use of cinema therapy in working with children with mental disorders. The objective of the work is to identify and analyze approaches, theories and concepts of cinema therapy used in working with children with mental disorders. The article explores the real theoretical constructs of cinema therapy in working with children with mental disabilities. The methods used are: a comparative method for comparing approaches, theories and concepts of cinema therapy in different countries; the historical method as a way of studying historical patterns through specific manifestations of historical facts in the form of the emergence and development of cinema therapy approaches, theories and concepts; analysis method as analysis of an integral object of cinema therapeutic theory into parts for its detailed study; a synthesis method as a process of combining disparate concepts of cinema therapeutic theories into a whole; a systematization method as an organization of the studied theoretical approaches of cinema therapy into a specific system; typologization method for identifying similar and distinctive features in approaches, theories, concepts of cinema therapy. The following approaches have been used: the structural-functional approach of T. Parsons and E. Shils, the concept of a representative culture of F. Tenbrook, and the systems theory of society as a communication of N. Luman. The research has shown that approaches, theories and concepts of cinema therapy are used basically in work with minors with mental disabilities, and the characteristics of these theoretical foundations for the use of cinema therapy are tightly connected with the practical implementation of the methods and ways of cinema therapy in working with such clients.